Challenges of Dairy farms in Bangladesh: a study of selected small scale dairy farms at Birulia Union of Savar Upazila. - Bhuiyan, Md. Ataur Rahman (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2018.